2020
DOI: 10.1111/tmi.13484
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory predictors of 30‐day mortality in severe acute malnourished children with severe pneumonia

Abstract: Objective To determine the predictors of mortality within 30 days of hospital admission in a diarrhoeal disease hospital in Bangladesh. Methods Cohort study of hospitalised children aged 0–59 months with severe acute malnutrition (SAM) and severe pneumonia in Dhaka Hospital, icddr,b, Bangladesh from April 2015 to March 2017. Those discharged were followed up, and survival status at 30 days from admission was determined. Children who died were compared with the survivors in terms of clinical and laboratory biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Eighty-eight percent of our enrolled patients were discharged from hospital after recovery, 3% left against medical advice, 5.4% referred to other medical facility and remaining 5.4% expired. This proportion of hospital outcome is similar to that of other published report from this study site [14]. Our results demonstrated that children who received IV amoxicillin and IV gentamicin experienced 56% less treatment failure than children who received IV ampicillin and IV gentamicin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Eighty-eight percent of our enrolled patients were discharged from hospital after recovery, 3% left against medical advice, 5.4% referred to other medical facility and remaining 5.4% expired. This proportion of hospital outcome is similar to that of other published report from this study site [14]. Our results demonstrated that children who received IV amoxicillin and IV gentamicin experienced 56% less treatment failure than children who received IV ampicillin and IV gentamicin.…”
Section: Discussionsupporting
confidence: 91%
“…The patients usually presented with diarrhea, pneumonia, malnutrition, sepsis, and other associated complications and received free of cost treatment from the hospital. Details of the other facility of the settings are described elsewhere [14]. A data safety and monitoring board (DSMB) worked independently to monitor serious adverse events (SAE)s related to treatment.…”
Section: Study Settingsmentioning
confidence: 99%
“…Out of 191 children, 6% died within 30 days of admission (14/191). In our study 24 (9.9%) and 3 (3.4%) children from the PD group and PO group, respectively died, which is almost similar to the rates that documented by others [22]. This is an important but unsurprising observation of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Studies found that septic children are at risk of mortality both during and after hospitalization [ 5 ]. The post-discharge mortality rate varies between 7–43% in the 1st year [ 15 ] and 82% within five years [ 7 , 33 ]. Nearly half of the patients admitted to the Intensive Care Unit (ICU) of the Dhaka Hospital of icddr,b present with sepsis, and despite standard care, some septic children develop septic shock [ 11 ].…”
Section: Discussionmentioning
confidence: 99%